1975
DOI: 10.1007/bf00433892
|View full text |Cite
|
Sign up to set email alerts
|

An electron microscope study of ?Pacinian neurofibroma?

Abstract: An electron microscope study has been made of the "Pacinian neurofibroma". Unlike the usual neurofibroma the "Pacinian neurofibroma" is characterized by a proliferation of the so-called perineurial cells. Groups of surface vesicles, the absence of mesoaxons and a fragmented basallamina differentiate these perineurial cells from Schwann cells. The formation of the perineurial cells can be traced continuously from small and wide submicroscopic cellbands and clubshaped thickenings to ribbonlike cell complexes as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1975
1975
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Tumors arising from a peripheral nerve sheath can contain these cells in various proportions, as found in many ultrastructural studies [9,15,18,25,32,36,37]. Moreover, some authors [9,15] have also observed additional cells that had ultrastructural features interpretable as transitional stages among the three main cell types.…”
Section: Discussionmentioning
confidence: 88%
“…Tumors arising from a peripheral nerve sheath can contain these cells in various proportions, as found in many ultrastructural studies [9,15,18,25,32,36,37]. Moreover, some authors [9,15] have also observed additional cells that had ultrastructural features interpretable as transitional stages among the three main cell types.…”
Section: Discussionmentioning
confidence: 88%
“…In order to establish this, it would be of interest to investigate cases of Pacinian neurofibromas and nerve sheath myxomas, rare peripheral nerve lesions, which are thought to be derived mainly from the perineurium (Harkin & Reed 1969, Weiser 1975, Lazarus & Trombetta 1978. Many of the original descriptions of anti-EMA antibodies failed to report staining of the perineurium (Heyderman et al.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of cell interrelationships the present and previous electron microscopic studies have now demonstrated that benign peripheral nerve sheath tumors may be composed of Schwann cells alone8*24*25.27 of Schwann cells with concommitant fibroblastic proliferation 11917* 21,26,29,32.40 or of perineurial cells alone. 41 It would seem appropriate that the latter tumors should be placed in a category of their own, making three divisions of these tumors by electron microscopy: Schwannomas, neurofibromas and perineuriomas.…”
Section: Discussionmentioning
confidence: 99%